KEPEMIMPINAN TRADISIONAL JAWA-ISLAM DALAM MASYARAKAT JAWA - Wahyudi, Sarjana Sigit (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
In Indonesia, especially in Central Java, there are plural societies which need the presence of a leader who fits them best. Therefore, a figure who has the characteristics of leadership which fits the interest of his supporters is needed. The characteristics of leadership offered here are the traditional and Islamic model, including the model of â€œetika kedzaifan.â€ A figure, tipology, and characteristics which are embedded in the mind of a leader are what the society need.